2019
DOI: 10.1111/jcmm.14504
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic functional and pathological changes of type 1 diabetic mice in growing and maturation time

Abstract: To detect the changes in the liver function in both male and female OVE26 mice from young to adults for better understanding of type 1 diabetes‐induced hepatic changes, OVE26 mice and wild‐type FVB mice were raised in the same environment without any intervention, and then killed at 4, 12, 24 and 36 weeks for examining liver's general properties, including pathogenic and molecular changes. The influence of diabetes on the bodyweight of male and female mice was different. Both male and female OVE26 mice did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…MDA, a marker of lipid peroxidation, was increased in the liver of T1DM mice, whereas the activity of antioxidant enzymes such as SOD and GPX was decreased. All these liver abnormalities are demonstrated by previous studies related to animal models of T1DM [27][28][29][30][31]. Furthermore, in previous clinical studies, T1DM patients showed decreased blood glutathione and cysteine, along with increased oxidative stress and lipid peroxidation [2], suggesting that oxidative stress or shortage of antioxidant defense systems and further activation of the inflammatory cascade might be the underlying mechanism of liver injury and dysfunction.…”
Section: Discussionmentioning
confidence: 76%
“…MDA, a marker of lipid peroxidation, was increased in the liver of T1DM mice, whereas the activity of antioxidant enzymes such as SOD and GPX was decreased. All these liver abnormalities are demonstrated by previous studies related to animal models of T1DM [27][28][29][30][31]. Furthermore, in previous clinical studies, T1DM patients showed decreased blood glutathione and cysteine, along with increased oxidative stress and lipid peroxidation [2], suggesting that oxidative stress or shortage of antioxidant defense systems and further activation of the inflammatory cascade might be the underlying mechanism of liver injury and dysfunction.…”
Section: Discussionmentioning
confidence: 76%
“…Previous studies that used Mri to measure hepatic fat content indicated that the prevalence of naFld in adults (111,112) and children patients with T1dM (113) did not increase. in a time-course study of OVE26 mice (a type 1 diabetic model) Oil red o staining and biochemical methods were used to detect the lipid content in the liver; the data indicated that uncontrolled T1dM did not cause lipid deposition in the liver, which was most likely due to the reduced lipid synthesis as a result of insulin deficiency (114). NAFLD must be distinguished from the more common glycogen hepatopathy, which is responsible for hepatomegaly and liver dysfunction in patients with T1dM (115).…”
Section: Increased Rates Of Hepatic Gluconeogenesis In Both T1dmmentioning
confidence: 99%
“…increased liver fat has been discovered to be associated with decreased insulin clearance and sensitivity in patients with T2dM (116,120), whereas in T1dM, which is characterized by decreased insulin secretion, the lipid synthesis in patients with T1dM was reduced (11,114,121). T1dM is characterized by insufficient insulin secretion and excessive glucagon production (2) and the mechanism of naFld in T1dM may be complicated; regnell and lernmark (122) proposed three hypotheses to explain the occurrence of hepatic steatosis in patients with T1dM.…”
Section: Increased Rates Of Hepatic Gluconeogenesis In Both T1dmmentioning
confidence: 99%
“…The average score for each group was measured to determine the total score. Lipid droplets were quantified as described by Jiang et al (17). Results are presented as area fractions, i.e., the percentage of specific counts in relation to total number of counted points.…”
Section: Animalsmentioning
confidence: 99%